2014
DOI: 10.3109/10903127.2014.980474
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Linkage of Prehospital and Outcomes Data in Out-of-hospital Cardiac Arrest

Abstract: Objective Lack of longitudinal patient outcome data is an important barrier in emergency medical services (EMS) research. We aimed to demonstrate the feasibility of linking prehospital data from the California EMS Information Systems (CEMSIS) database to outcomes data from the California Office of Statewide Health Planning and Development (OSHPD) database for patients with out-of-hospital cardiac arrest (OHCA). Methods We included patients age 18 years or older who sustained non-traumatic OHCA and were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 17 publications
0
12
0
6
Order By: Relevance
“…Linkage of existing prehospital OHCA with hospital administrative data is a potential tool but presents unique challenges with limited linkage capability. 21 Prospectively maintained ED-based or EMS-based registries are probably the best methods for compete identification of OHCA subjects. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Linkage of existing prehospital OHCA with hospital administrative data is a potential tool but presents unique challenges with limited linkage capability. 21 Prospectively maintained ED-based or EMS-based registries are probably the best methods for compete identification of OHCA subjects. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies have used ICD-9-CM code 427.5 listed as the principal diagnosis to identify OHCA cases. 15,16 Similarly, cardiac arrest may also be coded in patients with do-not-resuscitate (DNR) orders for whom no treatment is attempted. Furthermore, health data coders may not include code 427.5, preferring to rank other diagnoses codes higher (eg, comorbidities), which will skew the coded incidence of IHCA.…”
Section: Study Populationmentioning
confidence: 99%
“…These codes have been used in prior studies to identify patients with out-of-hospital cardiac arrest. 6, 7 Prior studies of state-wide databases as well as Medicare/Medicaid claims data have shown ICD-9-CM codes, using principal diagnosis, to be reliable in accurately identifying patients with OHCA. 810 All patients with concomitant diagnosis of injury were excluded.…”
Section: Methodsmentioning
confidence: 99%